Electro-spinning of highly-aligned polyacrylonitrile nano-fibres with continuous spooling - Siheng Shao (Nature Portfolio, 2021)
Abstract This paper reports on a new configuration for producing highly-aligned electro-spun fibres that can be produced on a static substrate or one where it is hauled off and spooled continuously to enable the production of continuous lengths. The fixture consists of a Vee-shaped polytetrafluorethylene shield at 60° with a 1 cm wide integral rectangular base that is mounted on a copper disk with a 10 cm diameter. Specified concentrations of polyacrylonitrile in dimethyl sulfoxide were electro-spun on to a strip of cellulose paper. In the static setup, approximately 91% of the fibres were deposited to within 3°. When the spooling rig was used, a tape of the cellulose paper was hauled off at 0.07 mm/min, 78% of the fibres were aligned to within 3°. Simulations of the conventional and Vee-shield electro-spinning setups were undertaken and they provided corroboration for the experimental observations with regard to the mechanism responsible for fibre alignment. The feasibility of using this technique to produce 0°/− 45°/+ 45° stacked layers of aligned fibre preform is demonstrated.